2011
DOI: 10.1111/j.1524-4725.2010.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Allograft and Overall Survival of Patients with Posttransplant Skin Cancer

Abstract: Longer early to mid-term allograft and overall survival was seen in patients with NMSC, but long-term survival rates must be examined to determine whether mortality rates increase later for patients with NMSC, as noted in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…The localization of cancer on the head and face may require complex surgical procedures, and the recurrence rate after surgery is increased in comparison to immunocompetent people (20). Death due to metastatic dissemination of SCC is rare, as observed in our cohort (Table 4), and the impact of NMSC on overall transplant related mortality and graft survival is uncertain (21)(22). Incidence rates of noncutaneous cancer in the present study were comparable to those reported in other studies, ranging from 13% at 10 years to 30% after 20 years (1-3).…”
Section: Discussionsupporting
confidence: 80%
“…The localization of cancer on the head and face may require complex surgical procedures, and the recurrence rate after surgery is increased in comparison to immunocompetent people (20). Death due to metastatic dissemination of SCC is rare, as observed in our cohort (Table 4), and the impact of NMSC on overall transplant related mortality and graft survival is uncertain (21)(22). Incidence rates of noncutaneous cancer in the present study were comparable to those reported in other studies, ranging from 13% at 10 years to 30% after 20 years (1-3).…”
Section: Discussionsupporting
confidence: 80%
“…The prolonged use of azathioprine has been associated with an increased risk of nonmelanoma skin cancer, which may be explained by a dual mechanism, including an increased DNA damage powered by the interaction between ultraviolet-A radiation and 6-thioguanine, and an impaired DNA repair system [59,60]. The actual implication of nonmelanoma skin cancer, which usually is diagnosed at early stages, on prognosis is a matter of debate [61,62]. In inflammatory bowel disease patients treated with azathioprine, there is a four- to five-fold increased risk of lymphoproliferative disorders, especially in elderly patients, but still lymphoma is a very uncommon malignancy [63].…”
Section: Antimetabolitesmentioning
confidence: 99%
“…CSA acts by binding to intracellular cyclophilin molecules -preventing the activation of the calcium-dependent phosphatase calcineurin -and inhibits the expression of immune-related cytokines such as IL-2 and IFN-γ (8,9). The use of these agents has been associated with an increased incidence of SCCs in particular primary cSCC, which occur proportionally to the intensity and duration of treatment (10,11). One proposed mechanism underlying the tumor-promoting effect seen with CSA use involves decreased tumor surveillance, which may occur as a result of diminished IL-2 production and systemic immunosuppression (12).…”
Section: Introductionmentioning
confidence: 99%